A flexible user interface for document-oriented applications. (2016) - Elfatatry, Ahmed
This work is concerned with software flexibility. Specifically, the focus is on the impact of changes in business requirements on user interface. The main objective is to propose and evaluate a flexible design that controls the propagation of changes in the business layer to the user interface layer in a flexible and consistent way. Many business applications that support flexibility in the business layer and also in the presentation layer fail to sustain flexibility across the boundary between the two layers. To address such problem, we introduced the presentation behaviour layer (PBL) as a solution for providing flexibility between the business layer and the presentation layer. The proposed solution addresses flexibility not only at each logical layer but also between different communicating layers. The PBL concept has been used to rebuild a real customs system. The evaluation shows enhancement in flexibility features of the new system compared to the old system.